Spear to the West: thought and recruitment in violent Jihadism - Chan, Stephen (Hurst & Company, 2019)
With the seeming defeat of ISIS, has jihadism disappeared from world politics? In this startling new book, Stephen Chan uncovers the ideological foundations that allow ISIS and other jihadi groups to survive, as they propagate terror by sophisticated means online and continue thrusting their spear at the West. Far from presenting simple-minded, black-clad fighters, Chan describes an elaborate process of online recruitment, which is, in its own terrible way, meaningful and thoughtful. He examines the foundations of this thought and the step-by-step methods of jihadi indoctrination, exposing the lack of IT knowledge among Western world leaders and urging the ‘moderate’ Islamic community in the West to challenge jihadi ideology with a courageous, non-violent ideology of its own. Without a counterideology, Chan argues, alienated Muslim youth are drawn not only to glamorised dreams of violence, but also to the pull of a totalising system of politics and theology. Spear to the West picks apart the fallacy of ‘thoughtless’ jihadi carnage, arguing that - dangerous and gruesome as it might be - there is more thought behind this phenomenon of destruction than meets the eye.